Effect of Phenol–Formaldehyde Molar Ratio on the Physicochemical Properties of Phenolic Synthetic Tanning Agent (Syntan) - Winata, Wahyu Fajar; Hermawan, Prasetyo; Nurbalia, Elis (EKSAKTA: Journal of Sciences and Data Analysis, 2026)
Phenolic synthetic tanning agents (syntans) are widely used in the leather industry due to their controllable properties and consistent performance. This study aims to investigate the effect of phenol– formaldehyde molar ratio on the physicochemical properties of syntans synthesized via sulfonation. The syntans were prepared using various molar ratios (0:1, 0.5:1, 1:1, 1.5:1, 1:0.5, and 1:0) throughcondensation followed by sulfonation. The products were characterized in terms of pH, specific gravity, viscosity, degree of sulfonation (DS), and functional groups using FTIR spectroscopy. The results show that increasing phenol or formaldehyde concentration led to higher specific gravity and viscosity, indicating increased polymerization. The pH values ranged around ~4, confirming suitability for leather processing. The DS decreased with increasing phenol or formaldehyde concentration, suggesting competition between polymerization and sulfonation reactions. The optimal molar ratio (1:1) produced the most homogeneous and stable syntan system. The pH values of all syntans were consistently around ~4, indicating suitability for leather processing. Increasing phenol or formaldehyde concentration resulted in higher viscosity and specific gravity, while the degree of sulfonation decreased significantly, confirming the trade-off between polymerization and sulfonation reactions. In conclusion, the phenol–formaldehyde molar ratio significantly influences syntan properties by controlling the balance between polymerization and sulfonation. These findings provide a scientific basis for optimizing syntan formulation and improving efficiency in sustainable leather processing.